Early Development of Dynamic Shape Perception under Slit-Viewing Conditions. (July 2014) - Imura, Tomoko; Shirai, Nobu
The developmental processes underpinning global shape and global motion perception in infancy have been relatively well described. However, the development of the ability to integrate both global motion and global shape information has remained unclear. In this study we employed a slit-viewing task to investigate the ability to integrate spatiotemporal information among infants ranging in age from 3 to 12 months. In experiment 1 each infant was familiarised with a moving object that was only partly visible through a slit. One of the two objects in the test trial was a novel object, and the other object had appeared previously in familiarisation trials. The findings suggested that infants aged 5 months and over looked longer at the novel drawings compared with the more familiar objects in the test trials. This implies that the infants recognised the whole shape of the object under the slit-viewing condition. In experiment 2 each infant was presented with partial images in a random order. In this case the infants were unable to distinguish the whole shape of the object. The findings suggest that infants did not rely on the local cues provided in experiment 1.